Reckless faith when the Church loses its will to discern - MacArthur, John F. 1939- (Wheaton, IL Crossway, 1994)
Includes bibliographical references and indexes.
Keywords: Discernment -- religious aspects -- Christianity; Evangelicalism -- theology